2022
DOI: 10.1024/0300-9831/a000688
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inflammatory index significantly affects lipids profile among adults: An updated systematic review and meta-analysis

Abstract: Abstract. Background: The available data on the relationship between dietary inflammatory index (DII®) and serum lipids are controversial. This systematic review and meta-analysis aimed to investigate the relationship between DII® and serum lipids, including total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) in general populations. Methods: PubMed, Web of Science, SCOPUS, and Cochrane electronic databases were systematically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 68 publications
0
0
0
Order By: Relevance
“…A recently published prospective population-based study showed that a pro-inflammatory diet was associated with an increased risk of dyslipidemia (59). In a meta-analysis, higher levels of DII were associated with higher levels of TG and LDL-C in apparently healthy populations (60). The relationship between DII and increased TG and decreased HDL-C has also been reported (61).…”
Section: Discussionmentioning
confidence: 92%
“…A recently published prospective population-based study showed that a pro-inflammatory diet was associated with an increased risk of dyslipidemia (59). In a meta-analysis, higher levels of DII were associated with higher levels of TG and LDL-C in apparently healthy populations (60). The relationship between DII and increased TG and decreased HDL-C has also been reported (61).…”
Section: Discussionmentioning
confidence: 92%